1911 N.Y. Laws 442-43, ch. 195, § 1 - (:unkn) unknown (General Publisher, 1911)
Prohibited the carrying or possession of any weapon of the kind commonly known as a blackjack, slungshot, billy, sandclub, sandbag, metal knuckles, or bludgeon, and the carrying or possession of any dagger, dirk, dangerous knife, razor, stiletto, or other “dangerous or deadly instrument or weapon” with intent to use the weapon unlawfully against another.
--
Keywords: CARRY - INTENT TO COMMIT CRIME - NON-GUN ARMS